2021
DOI: 10.3389/fneur.2021.696276
|View full text |Cite
|
Sign up to set email alerts
|

Motor Imagery: A Resource in the Fatigue Rehabilitation for Return-to-Work in Multiple Sclerosis Patients—A Mini Systematic Review

Abstract: Fatigue is a multidimensional symptom with both physical and cognitive aspects, which can affect the quality of daily and working life activities. Motor Imagery (MI) represents an important resource for use during the rehabilitation processes, useful, among others, for job integration/reintegration, of neurological pathologies, such as Multiple Sclerosis (MS). To define the effective rehabilitation protocols that integrate MI for the reduction of fatigue in patients with MS (PwMS), a literary review was perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 62 publications
0
11
0
Order By: Relevance
“…Multiple sclerosis (MS) is one of the most common causes of progressive neurological disability among young adults (1). Upper limb impairments, muscle weakness, spasticity, reduced functional performance, and fatigue are common clinical manifestations in patients with MS (2)(3)(4)(5)(6). A crucial impairment that might be often showed by patients with MS is balance disturbance, which could result in a higher risk of falling and reduced independence in the activities of daily living (ADLs) (7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…Multiple sclerosis (MS) is one of the most common causes of progressive neurological disability among young adults (1). Upper limb impairments, muscle weakness, spasticity, reduced functional performance, and fatigue are common clinical manifestations in patients with MS (2)(3)(4)(5)(6). A crucial impairment that might be often showed by patients with MS is balance disturbance, which could result in a higher risk of falling and reduced independence in the activities of daily living (ADLs) (7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…In patients with multiple sclerosis (MS) guided imagery increases walking speed and distance, reduces fatigue, improves the quality of life, and positively influences dynamic balance and perceived walking ability [35,36]. Imagery has also been used to identify and manage emotional aspects of MS possibly associated with symptoms worsening [37] as well as to counteract fatigue and facilitate return-to-work [38]. Fatigue is one of the greatest burdens for people with MS, is present in most of them, and is considered one of the worst symptoms by about half of patients, often disabling and interfering with daily life activity.…”
Section: Functional Equivalence Between Imagery and Perception/action...mentioning
confidence: 99%
“…Growing evidence has shown that exercise and physical activity are beneficial rehabilitation strategies for people with MS (pwMS) for managing symptoms, restoring function, optimising the quality of life, promoting wellness, and boosting participation in activities of daily living [4]. Recently, novel strategies such as MI have been used in pwMS [5][6][7]. Two J o u r n a l P r e -p r o o f recent systematic reviews in pwMS have demonstrated that MI shows positive effects on fatigue, walking, balance, quality of life, and return-to-work strategies [6,7].…”
Section: Introductionmentioning
confidence: 99%